One Year of SARS-CoV-2: Genomic Characterization of COVID-19 Outbreak in Qatar - Benslimane, Fatiha M.; Al Khatib, Hebah A.; Al-Jamal, Ola; Albatesh, Dana; Boughattas, Sonia; Ahmed, Ayeda A; Bensaad, Meryem; Younuskunju, Shameem; Mohamoud, Yasmin A.; Al Badr, Mashael; Mohamed, Abdalla A.; El-Kahlout, Reham A.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Qatar, a country with a strong health system and a diverse population consisting mainly of expatriate residents, has experienced two large waves of COVID-19 outbreak. In this study, we report on 2634 SARS-CoV-2 whole-genome sequences from infected patients in Qatar between March-2020 and March-2021, representing 1.5% of all positive cases in this period. Despite the restrictions on international travel, the viruses sampled from the populace of Qatar mirrored nearly the entire global population's genomic diversity with nine predominant viral lineages that were sustained by local transmission chains and the emergence of mutations that are likely to have originated in Qatar. We reported an increased number of mutations and deletions in B.1.1.7 and B.1.351 lineages in a short period. These findings raise the imperative need to continue the ongoing genomic surveillance that has been an integral part of the national response to monitor the SARS-CoV-2 profile and re-emergence in Qatar.